HARISH (Happy to Read English) as Learning Media on Reading Skill for Senior High School - Nur, Luluk Choirun Nisak; Ilma, Mafazatul; Ma'arif, Iin Baroroh (JoEMS (Journal of Education and Management Studies), 2023)
The aim of this research was to design reading materials for the eleventh grade students of Vocational High School TI An Najiyah Bahrul Ulum, Tambakberas, Jombang. The research used Research and Development method, the model used for designing the materials was ADDIE model that consist of analysis, design, development, implementation, and evaluation. The materials designed for reading skill. The researcher focused on designing reading material for first semester. Based on data development stage, the researcher got 81,3% on material validation and got 74,2% on media validation. After the product has been validated, the researcher tried out the product to know the respond of students toward the product. The student’s responses were 88% that could be categorized as “very good’. Based on the data, it can be summarized that this application is feasible and can be applied to Senior High School Level.